2010
DOI: 10.1007/s10096-010-0936-9
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell deformability in patients with human immunodeficiency virus infection

Abstract: Red blood cell (RBC) deformability is a major determinant of the ability of the RBC to pass repeatedly through the microcirculation. A decrease in RBC deformability leads to tissue perfusion and organ dysfunction. The purpose of this study was to measure the rigidity of RBCs from human immunodeficiency virus (HIV) seropositive individuals and investigate its relation to immune status and viral load. A filtration method based on the initial flow rate principle was used to determine the index of rigidity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Several human conditions can be characterized by the loss of RBC deformability, [24][25][26][27][28][29][30][31] with SCD being the most described 24 but also includes, HIV, T2D, and natural aging. [26][27][28][29][30][31] The presence of altered RBC membrane deformability in blood is not without consequences; increased RBC membrane rigidity has been linked to pulmonary vascular resistance, crisis pain in SCD, and lowered cardiovascular health. 54 Gutierrez et al recently reported that less deformable RBCs in blood severely reduced the adhesion of WBCs to an inflamed vessel wall in blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several human conditions can be characterized by the loss of RBC deformability, [24][25][26][27][28][29][30][31] with SCD being the most described 24 but also includes, HIV, T2D, and natural aging. [26][27][28][29][30][31] The presence of altered RBC membrane deformability in blood is not without consequences; increased RBC membrane rigidity has been linked to pulmonary vascular resistance, crisis pain in SCD, and lowered cardiovascular health. 54 Gutierrez et al recently reported that less deformable RBCs in blood severely reduced the adhesion of WBCs to an inflamed vessel wall in blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…RBC deformability is known to be drastically altered not only in certain diseases of genetic origin, such as sickle cell disease (SCD) and hereditary spherocytosis, 24,25 but also in others that developed upon a viral or parasitic invasion, such as human immunodeficiency virus (HIV) and malaria. 25,26 The RBCs in patients with Type 2 Diabetes (T2D) have also been reported to be significantly less deformable than healthy cells. 27 Metabolic disorders such as obesity and lifestyle habits such as smoking can also reduce the deformability of RBCs.…”
Section: Introductionmentioning
confidence: 99%
“…After two weeks of therapy 10 mL venous blood was taken for measurement of blood viscosity and other parameters. These are the following: hematocrit measurement: HCT haematocrit regarded as the red material in blood HCT g/L measured by microhematocrit tube at 10000/minutes RPM for five minutes [ 18 ]; total serum protein (TP) g/dL measured by automated analyzer (Nephstar Plus three-channel protein analyzer, Yima Opto-Electrical Technology Co. Ltd.) [ 19 ]; serum fibrinogen measured by Fibrinogen Human ELISA Kit (ab108841) [ 20 ]; measurement of blood viscosity, whole blood viscosity (WBV) [ 21 24 ]: measured by capillary viscometer (0.9 mm diameter, 51720/111 Schott-Gerate type) in relation to distilled water viscosity; relative viscosity = flow time of blood (sec)/flow time of D.W sec; actual viscosity = relative viscosity − D.W viscosity; D.W viscosity = 0.9615 cP; high shear rate: WBV = (0.12 × HCT%) + 0.17(TPg/dL−2.07); low shear rate: WBV = (1.89 × HCT%) + 3.76(TPg/L−78.42); kinematic viscosity ( v ) = actual blood viscosity ( η )/blood density ( p )[ 25 , 26 ]; blood density = 1.060 kg/m 3 at 37°C; kinematic viscosity: fluid viscosity without force references; RBC rigidity index (RRI) = blood viscosity/plasma viscosity [ 27 ]; plasma viscosity measured by low shear 30 viscometers at shear rate of 69.5 s −1 (automated viscometer); …”
Section: Methodsmentioning
confidence: 99%
“…Diseases involving rigid RBCs are typically of a genetic origin and have been studied mostly from this biological perspective, with their genetic nature limiting treatment options and efficacy . Patients inflicted with sickle cell disease (SCD), hereditary spherocytosis, iron-deficient anemia, pyruvate kinase deficiency, human immunodeficiency virus (HIV), malaria, sepsis, and even natural aging have less deformable (rigid) RBCs than healthy patients. It is well-known that rigid RBCs cause major physical damage when traveling through the body by occluding microvasculature, depriving tissues of nutrients, and damaging walls of the spleen, liver, and lungs. , This damage produces further complications such as pulmonary hypertension and cardiac dysfunction. , However, to date, there is little understanding of the direct impact of RBC rigidity on the functionality of other blood cells and the downstream contribution to disease manifestation beyond the occlusion of microvasculature …”
Section: Introductionmentioning
confidence: 99%
“…Recent computational works have begun to elucidate the transport mechanisms of cell types with different physical properties in blood flow and have underlined the major impact of cell size and rigidity on blood margination. ,, However, there are many challenges to modeling such highly complex fluid flow as human blood accurately, e.g., selection of appropriate boundary conditions and appropriately modeling the multiphase composition of blood. The ability to fully elucidate the effects of cellular rigidity and shape on hemodynamic blood margination can offer useful insight into the pathology of the many diseases in which RBC rigidity has been implicated, including in SCD that is the most described disease associated with altered RBC deformability.…”
Section: Introductionmentioning
confidence: 99%